2001
DOI: 10.1002/1521-396x(200109)187:1<305::aid-pssa305>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Dimer Production in a Poisoned Catalytic Model

Abstract: We studied a catalytic reaction model among three monomers on a square lattice using Monte Carlo simulations. Our model consists in the introduction of an irreversible adsorption step to the well known Ziff, Gulari, and Barshad model. In this step, the third monomer blocks one site on the catalytic surface. Besides, we also allow for the diffusion of the monomers on the surface. This model does not present a phase transition, because the steady states are always poisoned for any value of the adsorption rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Our approach is based on the Ziff, Gulari and Barshad model (ZGB model) [11] for the irreversible oxidation of carbon monoxide on a catalytic surface. Besides, as the gaseous reservoir contain three types of molecules (O 2 , NH 3 and NO), we also used the ideas proposed by Schmidt and Santos [12] to study the poisoning of a catalytic surface when a third nonreactive monomer is present in the gaseous reservoir.…”
Section: Introductionsupporting
confidence: 73%
“…Our approach is based on the Ziff, Gulari and Barshad model (ZGB model) [11] for the irreversible oxidation of carbon monoxide on a catalytic surface. Besides, as the gaseous reservoir contain three types of molecules (O 2 , NH 3 and NO), we also used the ideas proposed by Schmidt and Santos [12] to study the poisoning of a catalytic surface when a third nonreactive monomer is present in the gaseous reservoir.…”
Section: Introductionsupporting
confidence: 73%
“…Notice how the impurities act as a barrier between the CO and O sites, preventing them from reacting. It has been shown that, when CO and O are allowed to diffuse on the surface, there can be a moderate reaction rate, even in the case that the impurities do not desorb [21].…”
Section: Amentioning
confidence: 99%
“…Other authors have applied a similar approach. They found that the reaction window of the model shrinks with increasing contaminant concentration, and that the high-y transition changes from discrete to continuous [20][21][22]. Although some of these studies introduce the possibility that the impurities desorb from the surface, they do not analyze in detail the effects of the desorption.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these models assume that the impurities are present in different concentrations on the catalytic surface. In this work we analyze the problem in a more realistic way by assuming that the impurities are part of the gas mixture [44][45][46]. The impurities can be adsorbed or desorbed, but otherwise they do not take part in the reaction.…”
Section: Introductionmentioning
confidence: 99%